Strategic customer service managing the customer experience to increase positive word of mouth, build loyalty, and maximize margins and profits - Goodman, John A.; Broetzmann, Scott M. (HarperCollins Leadership, an imprint of HarperCollins, 2019)
Any organization can win more customers and increase sales if they would only learn to be more strategic with their customer service. This book draws on over 30 years of research from companies such as 3M, GE, and Chick-Fil-A to teach readers how to transcend a good business into a profitable word-of-mouth machine that transforms the bottom line. When customers complain, employees respond. The typical service model is riddled with holes. What about people and businesses who never speak upbut never come back' Learn to actively reach out, prevent problems, and resolve issues in ways that boost loyalty. Transform customer service into a strategic function, and reap benefits far exceeding investments'often 10 to 20 times more. Strategic Customer Serviceis a data-packed roadmap that shows you how. This new edition of a landmark book distills decades of research on the impact of great versus mediocre service. Complete guidelines and case studies explain how to: gather and analyze customer feedback; empower employees to fix problems; track your impact on revenue; generate sensational word of mouth; tap opportunities to cross-sell and up-sell; and more. Updated sections help you forge bonds via social media and online chat, attract and retain great employees, and leverage the latest technology. Why settle for passive service' Make a business case for ramping up operations'and get the tools for making it pay off.